2018
DOI: 10.14336/ad.2017.0808
|View full text |Cite
|
Sign up to set email alerts
|

Progression of White Matter Hyperintensities Contributes to Lacunar Infarction

Abstract: Both white matter hyperintensities (WMHs) and lacunar infarctions (LIs) are magnetic resonance imaging (MRI) markers of cerebral small vessel disease (SVD). However, the association between WMH and LI remains unclear. In this study, we asked whether WMH progression is related to LI occurrence using retrospective data. Overall, 8475 WMH patients with at least two MRI images were screened, and 187 patients were included in the final study; 76 patients had WMH with LI (WL), and 111 patients had WMH without LI (WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Recent findings have indicated that WMHs are associated with the cognitive impairment in CSVD [4,[29][30][31], and our results (Fig. 3D, E) are consistant with these findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recent findings have indicated that WMHs are associated with the cognitive impairment in CSVD [4,[29][30][31], and our results (Fig. 3D, E) are consistant with these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Worldwide, the number of CSVD patients is more common in Asians than in Caucasians [5]. Growing evidence has shown that systemic inflammatory mediators such as superoxide dismutase (SOD) and lipoprotein-associated phospholipase A2 (Lp-PLA2) are associated with CSVD and cognitive impairment [4,[6][7][8]. However, the role of Lp-PLA2 and SOD, especially SOD, in CSVD patients with cognitive impairment is largely unknown.…”
mentioning
confidence: 99%
“…(3) internal carotid artery or vertebral artery stenosis (>50%) or coronary atherosclerosis heart disease; (4) WMH due to immune-mediated inflammatory demyelinating disease (multiple sclerosis, neuromyelitis optica, acute disseminated encephalomyelitis), metabolic leukodystrophy and genetic leukoencephalopathy; (5) other neurological disorders, such as AD, Parkinson's disease, epilepsy; (6) systemic disease, such as cancer, shock, and anemia; (7) prominent impairments of audition or vision.…”
Section: Participantsmentioning
confidence: 99%
“…Increasing evidences have confirmed that WMH can lead to cognitive impairment (CI) and is associated with an increased prevalence of stroke, dementia, and death (5,6). Additionally, different lesion sites of WMH are closely related to different cognitive aspects.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of studies have reported that WMH can cause vascular cognitive impairment (CI), especially in domains of executive function, attention, working memory and information processing speed. Furthermore, WMH is correlated closely with increased prevalence of stroke, dementia, and death [6,7]. WMH is known to be highly related to age [8], as well as independently related to risk factors for cardiac and cerebral vascular disease [9,10].…”
Section: Introductionmentioning
confidence: 99%